Central hyperthyroidism due to an ectopic TSH-secreting pituitary tumor: a case report and literature review - Zhu, Chonggui; Liu, Tong; Yu, Haonan; Chang, Lina; Zhang, Xiaona; Yao, Jia; Zhang, Geng; Chen, Qiusong; He, Qing; Liu, Ming (Frontiers in Endocrinology, 2024)
Ectopic Thyroid-stimulating hormone (TSH)-secreting tumors are extremely rare, with only 15 reported cases in the literature. Herein, we described a 60-year-old female patient with thyrotoxicosis and elevated or unsuppressed levels of TSH.Family history, laboratory and genetic tests did not support a diagnosis of resistance to thyroid hormone (RTH). Given the unsuppressed TSH, TSH-secreting tumor was suspected and magnetic resonance imaging(MRI) of the pituitary gland was performed. Surprisingly, the MRI scans revealed a nodule in the nasopharynx rather than a pituitary tumor in the sella region. Further evaluation using Gallium-68 DOTATATE positron emission tomography/computed tomography( 68 Ga-DOTATATE PET/CT) demonstrated increased DOTATATE uptake in the nasopharyngeal nodule.Additionally, an octreotide suppression test(OST) revealed a obvious reduction in TSH levels, further supporting the suspicion of the nasopharyngeal mass as the cause Ectopic TSH-secreting pituitary tumor 2 of inappropriate TSH secretion. To prepare for surgery, the patient received preoperative administration of octreotide, resulting in the normalization of TSH and thyroid hormone levels. The patient subsequently underwent successful surgical removal of the nasopharyngeal mass. Following the procedure, the patient experienced complete resolution of hyperthyroidism symptoms, with TSH declined and thyroid hormone levels returned to normal. Histochemistry analysis of the tumor revealed positive staining for TSH, growth hormone (GH), prolactin (PRL), luteinizing hormone (LH) and somatostatin receptor 2 (SSTR2). We discussed differential diagnosis of hyperthyroidism due to inappropriate TSH secretion, with a particular emphasis on the importance of 68 Ga-DOTATATE PET/CT in combination with OST for identifying ectopic pituitary tumors.